Clinical and radiographic evaluation of triple antibiotic paste pulp therapy compared to Vitapex pulpectomy in non‐vital primary molars - Ohoud T. Sijini; Heba J. Sabbagh; Khlood K. Baghlaf; Amina M. Bagher; Azzah A. El‐housseiny; Najlaa M. Alamoudi; Sara M. Bagher (Wiley, 2021)
Abstract Objectives This study compared and evaluated the clinical and radiographic efficacy of non‐instrumentation triple antibiotic paste pulp therapy and Vitapex pulpectomy in non‐vital primary molars. Material and Methods Healthy, 5-9 years old children with at least one non‐vital primary molar were included in the study. Molars were divided into two groups based on the subject's cooperation level. In the first group, molars received triple antibiotic paste, and a second group received Vitapex pulpectomy followed by a stainless‐steel crown. Triple antibiotic paste was freshly prepared and proportioned in equal parts by volume (metronidazole, minocycline, and ciprofloxacin = 1:1:1) before the scheduled treatment. A clinical and radiographic examination was performed by two trained and calibrated pediatric dentists at the pre‐operative baseline and the 6‐ and 12‐month follow‐up visits. Results A total of 28 molars received triple antibiotic paste pulp therapy and 20 received Vitapex pulpectomy. At the 6‐month follow‐up, the success rate among the molars in the triple antibiotic paste group was clinically (92.85%) and radiographically (85.71%) higher compared to the Vitapex group (91.67%, 62.50% respectively) with p = 0.89 and 0.55 respectively. At the 12‐month follow‐up, the molars in the triple antibiotic paste group showed lower clinical (95.45%) but higher radiographic success rate (72.73%) compared to the Vitapex group (100% and 62.50%) with (p = 0.85 and 0.47) respectively. None of the differences were statistically significant. Conclusions Both triple antibiotic paste and Vitapex can be clinically and radiographically effective in treating non‐vital primary molars.